STRATEGY OF INTEGRATED MARKETING COMMUNICATION TO INCREASE BRAND AWARENESS IN MILLENIAL GENERATIONS - Mamduh, Naufal; Hutagalung, Inge (IJRDO - Journal of Social Science and Humanities Research, 2020)
The focus of this research is the Integrated Marketing Communication (IMC) strategy related to brand awareness among the millennial generation. The research approach is qualitative with case study method and the research paradigm is constructivism.The results showed that the IMC strategy related to brand awareness among the millennial generation followed the behavior of millennial generation consumers. Company applies the six IMC components in marketing activities through retail and online as well as applies the AIDDA message processing model. The communication pattern of the millennial generation in processing messages from company's IMC strategy due to brand awareness occurs in digital and conventional spaces. The interesting components of IMC are sales promotion, personal selling and publicity.The constraints in implementing IMC strategy from the producer side are that millennial generation consumers prefer online shopping and have difficulty accessing smartphone credit services. Meanwhile, from the consumer side, constraints occur in the application of personal selling and advertising which is not optimal.